Psychological flexibility and attitudes towards individuals with disabilities - Fuchs, Hila (Kultura-Społeczeństwo-Edukacja, 2022)
This study examines the relationship between psychological flexibility and attitudes, perceptions, and feelings towards individuals with disabilities and towards integrating people with disabilities in society. This integrated study, presented here, is a stage in a broader study that examined the relationship between psychological flexibility, educational elements, and various components that take part in shaping and assimilating perceptions and attitudes towards disabilities. The study presented here was conducted in two parts: The first part included data collection and quantitative analysis from 153 adult subjects to understand the statistical relationship between psychological resilience and attitudes toward disability. The second part included integrated data collection and analysis, quantitative and qualitative, from 60 respondents, 30 children, and 30 adults, to deepen our understanding regarding the correlations between psychological flexibility and the approach towards disabilities and the understanding of components that affect the correlation. The study shows a positive correlation between psychological flexibility and an attitude towards disabilities, and contributes to deepening the understanding of components that have different effects on this relationship.